Variable Response of Kochia Accessions to Dicamba and Fluroxypyr in Western Kansas - V. Kumar; P. W. Stahlman; R. Currie; R. Engel; G. Boyer (Kansas Agricultural Experiment Station Research Reports, 2018)
The rapid development of glyphosate resistance in kochia has increased the use of auxinic herbicides (dicamba and fluroxypyr) in the US Great Plains, including Kansas. Increasing reliance on auxinic herbicides for controlling glyphosate-resistant (GR) kochia may also enhance the evolution of resistance to these herbicide chemistries. The main objectives of this research were to (1) investigate the variation in kochia response to dicamba and fluroxypyr, and (2) characterize the dicamba resistance levels among progeny of kochia accessions collected from western Kansas. Greenhouse experiments were conducted at the Kansas State University Agricultural Research Center near Hays, KS. Discriminate-dose studies with field-use rates of Clarity (dicamba) (16 fl oz/a) and Starane Ultra (fluroxypyr) (0.6 pt/a) indicated that progeny from individual kochia plants (accessions) collected near Garden City, KS, had 78 to 100% and 85 to 100% survivors when treated with dicamba and fluroxypyr herbicides, respectively, at 28 days after treatment (DAT). In separate dicamba dose-response experiments, two putative dicamba-resistant (DR) kochia accessions viz., DR-110 and DR-113 collected near Hays, KS, had about 5- and 3-fold resistance to dicamba, respectively, based on fresh weight reduction (I50)compared to a dicamba-susceptible (DS) accession. Based on plant dry weight response, the DR-110 and DR-113 accessions showed 9- and 6-fold resistance to dicamba, respectively. These results confirm the co-evolution of cross-resistance to dicamba and fluroxypyr in kochia accessions from Garden City, and moderate to high level resistance to dicamba in the Hays accessions. Growers should adopt stewardship programs for auxinic herbicides and utilize all available weed control tactics to prevent further evolution of auxinic resistance in kochia populations.